Efficacy and safety of polymer-free amphilimus-eluting stent in patients with and without diabetes mellitus: A prospective, multicenter observational study - Subin Lim; Ju Hyeon Kim; Soon Jun Hong; Jung-Joon Cha; Hyung Joon Joo; Jae Hyoung Park; Cheol Woong Yu; Do-Sun Lim; Jae-Youn Moon; Soon Yong Suh; Jin Man Cho (PLoS ONE, 2025)
Background Patients with diabetes mellitus (DM) undergoing percutaneous coronary intervention face higher risks of restenosis and adverse cardiovascular outcomes compared to those without DM. This study compared the real-world safety and effectiveness of the Cre8/Cre8 EVO stents in patients with and without diabetes. Methods We performed an investigator-initiated, prospective, single-arm observational trial at 28 sites in South Korea. The primary endpoint was a composite of cardiac death, target vessel-related myocardial infarction (MI), and any clinically driven repeat revascularization at 12 months. All-cause mortality was a key secondary endpoint. The adjusted outcomes of DM and non-DM groups were compared using 1:1 propensity score (PS) matching. Results A total of 2,043 patients (66.0 ± 11.5 years of age; 76.2% male) were analyzed. Diabetic patients (n = 773; HbA1c 7.3 ± 1.4%) were more likely to be older, female, and have hypertension, dyslipidemia, or chronic kidney disease. Among these, 20.2% (156 patients) were using insulin. There were 54 cases of primary endpoint, 22 (cumulative incidence, 3.4%) in the DM group and 32 (3.0%) in the non-DM group (p = 0.61). The DM group exhibited a higher all-cause mortality rate compared to the non-DM group (2.1% vs. 1.3%; p = 0.19). The adjusted risk of 1-year primary endpoint was similar between the DM and non-DM groups (hazard ratio, 1.20; 95% confidence interval, 0.63–2.30), with comparable safety profiles. Conclusion In this real-world study, the DM group treated with amphilimus-eluting stents demonstrated sufficient safety and effectiveness at 12 months, with a similar occurrence of cardiovascular events compared to the non-DM group.